The Interplay of Policy and Institutions during COVID-19 - Fang, Sheng; Peng, Mike W.; Xu, L. Colin; Yi, Yuanyuan (Taylor and Francis, 2022)
Are COVID-19 spread and mortality related to different countries’ government mobility restriction policies, democratic institutions, and cultural norms? Leveraging data from 140 countries, we find that policy, institutions, and vulnerabilities interact to determine pandemic spread and mortality. A delay in restricting international mobility increases pandemic mortality. Combining vulnerabilities with a delay in domestic mobility restrictions increases mortality. Democratic countries have faster policy responses and lower pandemic mortality, but they also face more adverse effects from a delay in restricting domestic mobility. More individualistic countries have a higher pandemic spread, and their delay in domestic mobility restrictions is associated with higher pandemic mortality.